Methods of Calculating Moisture Discharge Characteristics of Insulators - Shevchenko S.; Danylchenko D.; Hanus R.; Radohuz S.; Tomashevskiy R.; Makhonin M.; Potryvai A. (Problems of the Regional Energetics, 2025)
The article discusses methods for calculating the moisture discharge voltage of insulators under various operating conditions (pollution, humidity, etc.) to identify patterns of environmental influence on operational characteristics, as well as to improve the reliability and safety of power grids. The main aim of the study is to compare two approaches to calculating the moisture discharge characteristics of insulators: the classical method based on the Tepler formula and an alternative approach that utilizes generalized parameters. These parameters can be easily obtained from the technical characteristics of insulators or design standards for automated calculations. To achieve this goal, the authors addressed several important tasks. First, a comprehensive analysis of the behavior of electrical discharges on the surface of insulators under various operating conditions, including standard and adverse environments, was conducted. Second, an automated tool was developed to quickly and accurately determine the values of moisture discharge voltage. Third, the proposed method was experimentally validated using the LK 70-110 insulator. The tests revealed a discharge voltage of 549 kV and an electric field intensity of 2.1 kV/cm, confirming the accuracy of the calculation method. The key findings of the study highlight the importance of considering factors such as the properties of insulator surfaces and the degree of contamination, especially in underground substations where humidity and pollution exhibit specific characteristics. The proposed approach proved effective both in standard and challenging operating conditions. The significance of the results lies in the creation of a tool that simplifies the calculation of moisture discharge characteristics of insulators.